Love your Enemies - Seitz, O. J. F. (New Testament studies, 1969)
This study proposes a re-examination of the teaching of Jesus about showing love toward enemies, with a view to recovering if possible its historical background and original setting. As a first step to such recovery it appears necessary to consider numerous issues raised by form-critics and others regarding the present framework of the two compilations of sayings in which this teaching is preserved, namely the Matthean ‘Sermon on the Mount’ and its shorter Lukan counterpart, the ‘Sermon on the Plain’.